2017
DOI: 10.1103/physrevb.96.134425
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence consistent with a magnon Nernst effect in the antiferromagnetic insulator MnPS3

Abstract: A magnon Nernst effect, an antiferromagnetic analogue of the magnon Hall effect in ferromagnetic insulators, has been studied experimentally for a layered antiferromagnetic insulator MnPS 3 in contact with two Pt strips. Thermoelectric voltage in the Pt strips grown on MnPS 3 single crystals exhibits non-monotonic temperature dependence at low temperatures, which is unlikely to be explained by electronic origins in Pt but can be ascribed to the inverse spin Hall voltage induced by a magnon Nernst effect. Contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 26 publications
2
69
1
Order By: Relevance
“…We anticipate more works to appear for NiPS 3 and other members of MPX 3 . For instance, recent studies have shown exciting possibilities of making field‐effect transistors, tunneling devices, and photodetectors, using MPX 3 .…”
Section: Challenges and Opportunitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…We anticipate more works to appear for NiPS 3 and other members of MPX 3 . For instance, recent studies have shown exciting possibilities of making field‐effect transistors, tunneling devices, and photodetectors, using MPX 3 .…”
Section: Challenges and Opportunitiesmentioning
confidence: 98%
“…We anticipate more works to appear for NiPS 3 and other members of MPX 3 . 126,127,131,[136][137][138][139][140][141] For instance, recent studies have shown exciting possibilities of making field-effect transistors, 136,142 tunneling devices, 143 and photodetectors, 135,144 using MPX 3 . Furthermore, some MPX 3 nanosheets have been predicted to become ferromagnetic semimetals depending on charge carrier doping.…”
Section: D-vdw Antiferromagnetsmentioning
confidence: 99%
“…The component of L ′ 12 represents the magnonic spin Nernst effect in AFs [60][61][62] where thermal gradients generate helical magnon Hall transport, and consequently, the total magnonic spin Hall current becomes nonzero. This arises from the opposite magnetic dipole moment σ = ±1 inherent to the Néel magnetic order in AF, and the effect is characterized or ensured by the Z 2 topological invariant 31,34,35,39,89 [Eq.…”
Section: Hall Conductances Of Magnonsmentioning
confidence: 99%
“…[111] and thermal generation of spin currents in AFs has been established experimentally in Ref. [51] using the spin Seebeck effect [52][53][54][55][56][57][58][59] , with the subsequent report [60][61][62] of magnonic spin Nernst effect in AFs. Moreover, on top of Brillouin light scattering spectroscopy 1,112,113 , using infrared camera, the realtime observation of spin-wave propagation is now possible and Ref.…”
Section: Estimates For Experimentsmentioning
confidence: 99%
See 1 more Smart Citation